Cochlear implantation in children without preoperative computed tomography diagnostics. Analysis of procedure and rate of complications. (November 2020) - Ehrmann-Müller, Desiree; Shehata-Dieler, Wafaa; Kaulitz, Stefan; Back, Daniela; Kurz, Anja; Kühn, Heike; Hagen, Rudolf; Rak, Kristen
Abstract: Introduction: To evaluate the safety in cochlear implantation without preoperative computed tomography diagnostics, which was implemented into the protocol of cochlear implantation in 2013, since in the year before, new evidence concerning the risks of ionizing radiation especially in children arose. Methods: In this retrospective data analysis 89 children under 36 months, which were cochlear implanted from 2008 until 2018 at a tertiary referral centre with a large cochlear implant program were analysed. Fortyfour of the children were implanted before the date of change in 2013 and 45 in the following years up to now. The data about the operative procedures, the postoperative care and the complication rate before and after implementation of the new protocol were compared. Results: Before the date of change in 2013, 100% of patients received preoperative CT diagnostics, in the following years 13.3%. No difference in the duration of surgery, the procedure related and the late complications between the two groups was identified. Conclusion: Cochlear implantation in very young children under the age of 36 months without preoperative radiological diagnostics by CT scan of the temporal bone is a safe procedure without additional risks for the patients.